Schizophrenia delays and alters maturation of the brain in adolescence - Douaud, G; Mackay, C; Andersson, J; James, S; Quested, D; Ray, M; Connell, J; Roberts, N; Crow, T; Matthews, P; Smith, S; James, A (Oxford University Press, 2009)
Early-onset schizophrenia appears to be clinically more severe than the adult-onset form of the disease. In a previous study, we showed that anatomically related grey and white matter abnormalities found in adolescents patients were larger and more widespread than what had been reported in the literature on adult schizophrenia. Particularly, we found novel structural abnormalities in the primary sensorimotor and premotor systems. Here, we tested alternative hypotheses: either this striking sensorimotor-related pattern is an artefact due to a better sensititivity of the methods, or apparent greater structural abnormalities in the early-onset population are specifically associated with earlier disease onset. Then, if we were to find such characteristic structural pattern, we would test whether these anatomical abnormalities would remain static or, conversely, show dynamic changes in the still developing brain. To address these questions, we combined a cross-sectional study of the brain structure for adolescent-onset patients (n=25) and adult-onset patients (n=35) and respective matched healthy subjects with a longitudinal study of adolescent-onset patients (n=12, representative subset of the cross-sectional group) and matched healthy controls for ≥ 2 years. Looking at differences between adolescent and adult patients' grey matter volume and white matter microstructure abnormalities, we first confirmed the specificity (especially in motor-related areas) and the greater severity of structural abnormalities in the adolescent patients. Closer examination revealed, however, that such great anomalies seemed to arise because adolescent patients fail to folow the same development time course as the healthy control group. Longitudinal analysis of a representative subset of the adolescent patient and matched healthy populations corroborated the delayed and altered maturation in both grey and white matters. Structural abnormalities specific to adolescent-onset schizophrenia in the sensori-motor cortices and corticospinal tract were less marked or even disappeared within the longitudinal period of observation, grey matter abnormalities in adolescent patients evoloving towards the adult-onset pattern as defined by recent meta-analyses of adult schizophrenia. Combining cross-sectional adolescent and adult datasets with longitudinal adolescent dataset allowed us to find a unique, abnormal trajectory of grey matter maturation regardless of the age at onset of symptoms and of disease duration, with a lower and later peak than for healthy subjects. Taken together, these results suggest common aetiological mechanisms for adolescent- and adult-onset schizophrenia with an altered neurodevelopmental time course in the schizophrenic patients that is particularly salient in adolescence.